Changes in the Market of Two and Three-wheeled Motor Vehicles in Europe at the Beginning of the 21st Century - Sławomir Dorocki (Entrepreneurial Business and Economics Review)
Objective: In recent years, the number of motorcycles in many countries has changed significantly. A particularly diverse situation has taken place in Europe. This diversification has been influenced by both economic and institutional conditions. The study aims to identify the main trends on the Powered Two or Three-Wheelers (PTW) market in the world. The study analyses the distribution of PTW in the world and tracks the changes in the PTW market in particular European countries between 2001 and 2014.